2018
DOI: 10.1111/spc3.12415
|View full text |Cite
|
Sign up to set email alerts
|

A fine balance: A review of shared housing among young adults

Abstract: Young adults in the Western world have adapted to financial constraint by sharing accommodation and combining resources. Far from traditional stigma associated with these households the social benefits are considered on a par with economic pragmatism. Until recently the literature on young peer group‐living was sparse. Due to a rise in research interest, the area is experiencing a period of invigoration, particularly with regard to how interpersonal relationships work in the close confines of domestic intimacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…One study in Austria found that students often perceive unfairness in how domestic chores are divided up (Mikula, Freudenthaler, Brennacher-Kroll, & Brunschko, 1997). Conflict around cleaning chores has been found in shared housing outside of university (Clark, Tuffin, Bowker, & Frewin, 2018) but not in university settings, to our knowledge. The current study demonstrates that conflict is not only common in student accommodation, but that poorly managed conflict can escalate to the point where individuals do not want to be at home.…”
Section: Discussionmentioning
confidence: 65%
“…One study in Austria found that students often perceive unfairness in how domestic chores are divided up (Mikula, Freudenthaler, Brennacher-Kroll, & Brunschko, 1997). Conflict around cleaning chores has been found in shared housing outside of university (Clark, Tuffin, Bowker, & Frewin, 2018) but not in university settings, to our knowledge. The current study demonstrates that conflict is not only common in student accommodation, but that poorly managed conflict can escalate to the point where individuals do not want to be at home.…”
Section: Discussionmentioning
confidence: 65%
“…Flat sharing is an example of simultaneous sharing consumption, as a flat is consumed by several renters. Typically, flat sharing involves two or more people who use a communal kitchen and bathroom with individual bedrooms that are off limits to other sharers, and the sharers assume equal responsibility for rent (Clark, Tuffin, Bowker, & Frewin, ). According to the criteria proposed by Bardhi and Eckhardt () to describe non‐ownership consumption, simultaneous sharing ranging from carpooling or collaborative learning to community gardens can be characterized by two social features: a substantial level of physical closeness between sharers and, despite its temporary nature, a longitudinal usage duration that may involve one or more episodes of access to the shared resource.…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
“…In addition to facilitating accrued rewards of interaction, perceived homophily can help reduce social intrusiveness given that people who are similar to a focal individual in terms of education, values and behaviors are more likely to respond in appropriate ways regarding privacy concerns (Guha & Wicker, ) and, in the case of flat sharing specifically, the expected degree of psychological and physical closeness (Clark et al, ; Pera et al, ). On the contrary, the behavioral inappropriateness possibly exhibited by dissimilar people may increase an individual's psychological discomfort and sense of privacy invasion or even reduce his or her self‐esteem, all of which manifestations of social intrusiveness (Gehlbach et al, ; Leonard, ).…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
“…Yet, researchers seem to ignore prevalent, but less conventional, household structures such as shared housing situations. Shared housing or flatting situations involve at least two people living in a house or apartment and sharing some parts of the living areas (e.g., bathrooms, kitchens or living rooms) but exclusively utilizing other areas (e.g., their own rooms; Clark, Tuffin, Bowker, & Frewin, 2018). Individuals living in such situations are generally unrelated, single, childless, employed or studying, and geographically flexible (Clark et al, 2018).…”
Section: The Role Of Households Shared Housing and Student Householdsmentioning
confidence: 99%
“…House sharing is especially characteristic for students in the UK (Heath et al, 2018) and the Netherlands (van Hulle et al, 2015;van Hulle, Hooft, Marchal, Zwaneveld, & Vijncke, 2017). However, even though shared housing is a growing phenomenon in Europe, literature on the social dynamics and interpersonal relationships involved in such situations seems to be scarce (Clark et al, 2018;Clark, Tuffin, Frewin, & Bowker, 2017) Even though shared households are different from familial households in their structures, in many respects these differences are minimal. In both types of households, chores and economic costs have to be negotiated, relationships can become quite complex and intimate, individuals live in close proximity to each other, and sharing relationships are often characterized by a sense of connectedness (Heath et al, 2018).…”
Section: The Role Of Households Shared Housing and Student Householdsmentioning
confidence: 99%